(3fRgI GdCacGQ aj TQM bQI GdCHUGQs - (3YHO GdbGOQ Hf eMeO Hf SGde GdeLdSis; (3YHO GdYRjR Hf YHO GdYRjR GddeWj,J (B880 (3g` s ((3eMeO GdCejf Hf GdSYjO s)
(3ChdgG (B:s
(3CeG HYO ajbhd GdYHO GdabjQ dGjNai Cf GdGTZGd HGdYdhe ef CTQa GdecGSH hTQa cd Yde EfeG gh HMSH GdeYdhe HYde GdSjQI GdfHhjI aVdg YXje , hNWHg LSje s
(3BNQgG (B:s
(3GfYbO GdELeGY Ydi CaVdjI aGWeI , hHbi GdNdGa Hjf YGFTI hNOjLI s
(3HgG BKGQ QWhHI TOjOIs
(3MhGagG eJBcdIs
(3HYV GdcdeGJ hGdahGUd HGdMeQIs
(3HgG fXGe GdJYbjHI s
(3fSNI bOjeI s
(3fGbUI GdBNQ s
Keywords: (3GdJGQjNs